2009
DOI: 10.1139/h09-014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ramadan fasting on physical performance and metabolic, hormonal, and inflammatory parameters in middle-distance runners

Abstract: The Ramadan fasting (RF) period is associated with changes in sleep habits and increased sleepiness, which may affect physical performance in athletes, and may induce metabolic, hormonal, and inflammatory disturbances. In 8 middle-distance athletes (25.0 +/- 1.3 years), a maximal aerobic velocity (MAV) test was performed 5 days before RF (day -5), and on days 7 and 21 of RF. The same days, saliva samples were collected to determine cortisol and testosterone concentrations before and after the MAV test. Blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 35 publications
6
92
3
1
Order By: Relevance
“…However, studies on Muslims practicing Ramadan fasting gave conflicting results, with some reporting beneficial effects on metabolism [Adlouni et al 1997[Adlouni et al , 1998Maislos et al 1993), and others reporting increased metabolic and endocrine dysregulation [Chennaoui et al 2009;Fedail et al 1982;Gumaa et al 1978]. The Islamic world extends over a wide range of geographic locations, with different dietary habits and social practices.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on Muslims practicing Ramadan fasting gave conflicting results, with some reporting beneficial effects on metabolism [Adlouni et al 1997[Adlouni et al , 1998Maislos et al 1993), and others reporting increased metabolic and endocrine dysregulation [Chennaoui et al 2009;Fedail et al 1982;Gumaa et al 1978]. The Islamic world extends over a wide range of geographic locations, with different dietary habits and social practices.…”
Section: Discussionmentioning
confidence: 99%
“…sprinting, dribbling and jumping), the decrement is often minimal and sometimes performance is unaltered or even improved [ [ 5 , 6 , 8 , 14 , 19 , 37 ] , while others have noted no change in body mass [ 10 , 23 , 24 , 32 ] , or in the body mass index [ 18 ] . The decrements in body mass observed during Ramadan have been attributed to fat loss [ 8 ] , due to an increase in lipid oxidation in response to fasting [ 24 ] . Alternatively, it has been suggested that lipid, carbohydrate and protein metabolism are not dramatically aff ected during Ramadan [ 29 ] .…”
Section: Activity Patterns Body Composition and Muscle Function Durimentioning
confidence: 99%
“…For instance, Al-Hourani HM surveys showed that body weight and BMI decreased noticeably during fasting periods (8).The reduction of body weight has been reported quite repeatedly, but the connection between weight loss and body fat reduction is not often studied (9). Inconsistent findings have also been reported, regarding the effects of fasting on body composition (10,11). Some investigations did not find any significant changes in body weight or body composition during Ramadan (10)(11)(12).…”
Section: Contextmentioning
confidence: 95%
“…Inconsistent findings have also been reported, regarding the effects of fasting on body composition (10,11). Some investigations did not find any significant changes in body weight or body composition during Ramadan (10)(11)(12). Effect of Ramadan on biochemical parameters is still a debatable issue.…”
Section: Contextmentioning
confidence: 95%